Environment-Aware CMT for Efficient Video Delivery in Wireless Multimedia Sensor Networks - Yuanlong Cao; Changqiao Xu; Jianfeng Guan; Fei Song; Hongke Zhang (International Journal of Distributed Sensor Networks)
Wireless Multimedia Sensor Networks (WMSNs) have gained significant attention with capabilities of retrieving video and audio streams, still images, and scalar sensor data but with challenge of high data loss. As more and more wireless devices are equipped with multiple network interfaces, multimedia delivery over multipath has been cognized as a more promising approach in wireless transmission. In this paper, based on the Concurrent Multipath Transfer (CMT) extension for Stream Control Transport Protocol (SCTP), we propose a novel environment-aware CMT ( e -CMT) to overcome the high data loss challenge, as well as “a hot potato” congestion problem in wireless transmission. The e -CMT provides environment-aware cognitive ability for efficient video delivery with three modules, which are Path Quality-aware Model (PQM) that devotes to estimate path quality and select candidate path using for retransmission, Adaptive Retransmission Trigger (ART) that contributes to cognize packet loss and trigger efficient retransmission behaviors, and Congestion-avoid Data Distributor (CDD) that serves to enable Partial-Reliable retransmission to mitigate congestion condition. We design a close realistic topology to present how the e -CMT outperforms the original CMT for efficient video delivery over multihomed WMSNs.